2015
DOI: 10.1586/1744666x.2016.1112268
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation, bioengineering and regeneration: an originally immunology-based discipline destined to transition towards ad hoc organ manufacturing and repair

Abstract: Kidney transplantation (KT), as a modality of renal replacement therapy (RRT), has been shown to be both economically and functionally superior to dialysis for the treatment of end-stage renal disease (ESRD). Progress in KT is limited by two major barriers: a) a chronic and burgeoning shortage of transplantable organs and b) the need for chronic immunosuppression following transplantation. Although ground-breaking advances in transplant immunology have improved patient survival and graft durability, a new path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…Recent studies have demonstrated that MSC-based therapy is one of the best candidates for regeneration and healing in CKD [ 24 , 25 ]. MSCs, which are a subcategory of adult stem cells, are widely used for organ regeneration and tissue repair due to their secretion of growth factors and cytokines, capacity for tissue-specific differentiation, and subsequent self-renewal ability [ 26 , 27 ]. This study has shown that pretreatment of MSCs with pioglitazone restored mitochondrial potential, and increased activation of complexes I/IV and mitophagy through up-regulation of PINK-1 under PC exposure conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that MSC-based therapy is one of the best candidates for regeneration and healing in CKD [ 24 , 25 ]. MSCs, which are a subcategory of adult stem cells, are widely used for organ regeneration and tissue repair due to their secretion of growth factors and cytokines, capacity for tissue-specific differentiation, and subsequent self-renewal ability [ 26 , 27 ]. This study has shown that pretreatment of MSCs with pioglitazone restored mitochondrial potential, and increased activation of complexes I/IV and mitophagy through up-regulation of PINK-1 under PC exposure conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental of ECM‐based scaffold application is that the decellularization procedure preserves the ECM frames, which retain vascular trees, basic structural proteins and polysaccharides, matrix‐bound growth factors and various cytokines 17,18 . Therefore, ECM can provide cues for cellular to differentiate, develop, and function 17,19,20 . Furthermore, it also can accelerate progenitor cells different into organ‐specific phenotypes 17,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the road to the ultimate objective appears long, winding and difficult (Figure 2), the different RM technologies are still immature and several questions will have to be answered before translation may occur (Table 1), the days when success will be the usual outcome are ahead of us and closer are the days when TM, a discipline that traditionally has been immunology-based [134,135], will realize that RM should become its major research core. If we agree on this, then TM should allocate more funds to RM-inspired research, transplant societies should twin with RM societies and established RM community of practices and committees, transplant journals and conferences should grant the due consideration and visibility to RM manuscripts.…”
Section: Discussionmentioning
confidence: 99%